Reintegration of ex-Military Personnel with Civil Life- A social Issue and Big Challenge: An Empirical Study - Dr. Priti Verma; Shahriar Al Imran (International Journal of Engineering and Management Research, 2020)
Every year a large number of individuals have to quit different military services: army, navy, air force etc. for different reasons all over the world. Among all the reasons, medical discharge is the most unacceptable one. After forced departure from the service, these personnel face several problems as they go through a difficult and sensitive time in their life. Starting from post-traumatic stress disorder (PTSD), they go through different mental, psychological, social and psychopathological problems. Further, people look at them in a different way when they come to know that the person had to resign from military services. Moreover, the behavior and attitude of the family members and relatives make the situation worse. Ex-military personnel of this category suffer from depression. However, the person can be turned into a positive and effective power of the society by proper support from the surroundings as the person can use the learning from his/her experience in other occupations as well. The paper draws attention towards this social problem. The benefits of the research will have an impact on the ex-military community of forced departure, as this problem has not been addressed properly in broader context before.